Management of bipolar I depression: clinical utility of lurasidone - Findlay LJ; El-Mallakh P; El-Mallakh RS (Dove Medical Press, 2015)
Lillian Jan Findlay,1 Peggy El-Mallakh,1 Rif S El-Mallakh2 1College of Nursing, University of Kentucky, Lexington, KY, USA; 2Department of Psychiatry and Behavioral Sciences, University of Louisville School of Medicine, Louisville, KY, USA Abstract: Lurasidone is a benzisothiazol derivative second-generation antipsychotic. It has been approved in the United States and Europe for treatment of acute schizophrenia and bipolar depression. In type I bipolar subjects, treatment with lurasidone monotherapy of adjunctive therapy to lithium or valproic acid with doses of 20 to 120 mg once daily with food, results in statistically and clinically significant reduction of depressive symptoms. Patients experience relatively few side effects, which include somnolence, akathisia, nausea, and other gastrointestinal upset. Dopamine related side effects, such as Parkinsonism and elevated prolactin, are rare and mild. Longer term safety data obtained in 6 months long, open continuation observation periods, suggest that metabolic related elevations in weight, glucose, and lipids are absent or minimal. The mechanism of action of lurasidone is not known, but the data are compatible with antagonism of the serotonin 7 receptor. Lurasidone is a new option for the treatment of bipolar depression with relatively few side effects. Keywords: lurasidone, bipolar disorder, bipolar depression, adjunctive therapy